The Inclusive Education Process Implementation Problems and Solutions to the Teachers’ Point of View - Rozenfelde, Mārīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Class teachers are the main resource to reach the goal of implementation of inclusive education in mainstream educational institutions. There will be different views and actions of teachers in any educational institution and we should not expect that everybody think and act in the same way. To implement inclusion in school a lot depends on teachers’ attitudes toward pupils with different needs, on whether teachers have necessary skills, competences, knowledge, pedagogical approaches, techniques, methods, materials that help to deal with diversity, whether a teacher has the necessary support inside and outside the school. In the article the issues of how teachers of mainstream schools in Latvia judge their ability to be inclusive; what challenges they see in their work and what kind of solutions they see on local and national level are emphasized. The article describes the overview study done by the author and it presents the findings and results of the study, the resolution of the scientific conference „Teacher in Inclusive Education” to promote implementation of inclusive education on national level supported by the participants of the conference.